2007
DOI: 10.1016/j.jvs.2006.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of a post-traumatic tibial pseudoaneurysm and arteriovenous fistula: Case report and review of the literature

Abstract: Here we report a rare case of a 74-year-old man with a pseudoaneurysm of the anterior tibial artery and a concomitant arteriovenous fistula (AVF). The patient was admitted because of increasing pain following the formation of a large mass located in the anterior mid-portion of the calf after a moderate non-penetrating blunt trauma. A polytetrafluoroethylene-covered stent was placed over the origin of the pseudoaneurysm, with complete exclusion of the pseudoaneurysm and disappearance of the AVF. One year after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 23 publications
2
50
0
4
Order By: Relevance
“…Good outcomes have been reported in lesions involving the tibioperoneal trunk, 2 posterior tibial artery 3,4 and ATA. 5,6 Spirito et al demonstrated the effective use of a covered stent graft for early treatment of an ATA AVF following a penetrating injury, similar to the lesion in our case, with graft patency and resolution of symptoms at a follow-up of 6 months. 6 Post-traumatic AVF is an uncommon complication and presentation after fracture of the lower limb.…”
Section: Images For Surgeonssupporting
confidence: 61%
“…Good outcomes have been reported in lesions involving the tibioperoneal trunk, 2 posterior tibial artery 3,4 and ATA. 5,6 Spirito et al demonstrated the effective use of a covered stent graft for early treatment of an ATA AVF following a penetrating injury, similar to the lesion in our case, with graft patency and resolution of symptoms at a follow-up of 6 months. 6 Post-traumatic AVF is an uncommon complication and presentation after fracture of the lower limb.…”
Section: Images For Surgeonssupporting
confidence: 61%
“…9 Recently, there have been an increasing number of reports of successfully treated crural artery aneurysm. 12,14,15 The advantages of the endovascular approach are the protection of the surrounding nerves and adjacent structures during repair and the minimal blood loss. Conversely, the disadvantages include the risk of thrombosing the narrow supplying artery either by stent-graft implantation or by transcatheter introduction of coils and a higher rate of failure.…”
Section: Discussionmentioning
confidence: 99%
“…Etiology seems to be related to trauma, bone surgery, infection or rare diseases. Due to the infrequent presentation, management guidelines are missing, and both open surgery 7 as well as endovascular treatment with coil embolization or stentgraft coverage 8 have been reported. To our knowledge this is the first report of a case presenting with aneurysmal degeneration of the distal anastomosis to a tibial artery with a Taylor patch.…”
Section: Discussionmentioning
confidence: 99%